2021
DOI: 10.1063/5.0063320
|View full text |Cite
|
Sign up to set email alerts
|

A novel gravity-assisted automatic docking device for studying diffusion in liquid metal melts assisted by a strong static magnetic field

Abstract: A novel gravity-assisted automatic docking (GAAD) method is presented for the study of interdiffusion processes in liquid Al–Cu melts. A novel GAAD device was designed to be suitable in a strong static magnetic field (SSMF) with a bore size of 50 mm. Energy dispersive x-ray spectroscopy was used to quantitatively analyze the concentration profiles of diffusion capillaries. The interdiffusion coefficient (DAlCu) was measured by applying Fick’s second law. The combination of SSMF and GAAD made the original diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The details of the GAAD apparatus can be found in Refs. [55,56]. Results demonstrated that the diffusionlimited condition as measured in microgravity was achieved when the MFD was greater than about 3 T. To further reveal the influence of this diffusive condition on crystal growth, Al-20wt.%Cu hypoeutectic alloy was solidified under a 24 T high SMF (Figure 3d-f) [61].…”
Section: Magnetic Braking Effect During Solidificationmentioning
confidence: 89%
See 3 more Smart Citations
“…The details of the GAAD apparatus can be found in Refs. [55,56]. Results demonstrated that the diffusionlimited condition as measured in microgravity was achieved when the MFD was greater than about 3 T. To further reveal the influence of this diffusive condition on crystal growth, Al-20wt.%Cu hypoeutectic alloy was solidified under a 24 T high SMF (Figure 3d-f) [61].…”
Section: Magnetic Braking Effect During Solidificationmentioning
confidence: 89%
“…Studies have shown that the diffusion coefficient value decreases with the increase in MFD, which provides a simulated diffusive condition [52][53][54]. Recently, a novel gravityassisted automatic docking (GAAD) device was independently developed to measure the interdiffusion coefficient of an Al-Cu alloy (D AlCu ) from 0 T to 22 T and the critical MFD for achieving the diffusion-limited condition [55,56], as shown in Figure 3a-c. The details of the GAAD apparatus can be found in Refs.…”
Section: Magnetic Braking Effect During Solidificationmentioning
confidence: 99%
See 2 more Smart Citations